A barreira Schottky na interface Al:nGaAs preparada por MBE - Vania Aguiar Moura (1992)
In onder to study mechanisms of Fermi levei pinnlg we haveprepared Intrerffiices belrween Al and nGaAs(100) by MBE .The Sahottkybarrier for different, sample t.emporatures is then obtained from I(V) andC(V). As the Schottky barrier is dependent, of interface conditions, wehave measured X-ray difraction of the Al film, in order to determine theAl film orietation . The character of pinning states has been interpreted in terms of the temperature coefficient of the band structure of semiconductor. We have observed that the Schottky barrier height is temperature independent and the results are discussed within the context of the current pinning model.